Influencia de un modelo del SGSI (norma ISO/IEC 27001:2013) en la eficacia de la administración de los recursos públicos. registro de la propiedad y mercantil del Cantón Pedro Moncayo, períodos 2019, 2020 y 2021. - Hidalgo Narváez, Mónica Patricia (2022)
This article demonstrates how the design and implementation of an Information Security Management System (ISMS) model under the international standard ISO/IEC 27001:2013 influences the effectiveness of public administration. For this, the ISMS model implemented by the Property and Mercantile Registry of the Pedro Moncayo Canton (RPMPM) has been taken as a reference; which, due to its operability in the management of public data, needed to obtain an international mark in Information Security (IS) and became a benchmark of good practices at the national level. The qualitative methodology describes the ISMS adopted by the RPMPM, under the standards of the ISO/IEC 27001: 2013 Standard and the integration with the Internal Control Standard (NCI) issued by the Comptroller General of the State (CGE), which at be applied are effective as the information is completely secure. In the same way, through the risk matrix and IS Committee minutes, the evolution of the ISMS is quantitatively analyzed before, during and after to ensure its correct implementation. To verify the benefits of these applications, a survey was formulated through Google to 200 people directly related to the ISMS, to determine the level of knowledge regarding the standard, and proposing an index prototype to evaluate the effectiveness of the public resources allocated to the IS, administered by the Registrars in Ecuador, determining that there is 93% (2020) and 100% (2021) of effectiveness by having the capacity to achieve the strategic objectives of IS and to contribute to the good government control. The data analyzed includes the periods 2019, 2020 and 2021.